Disciplined entrepreneurship : 24 steps to a successful startup - Aulet, Bill , 1958-; Ursache, Marius (John Wiley & Sons, 2013)
Disciplined Entrepreneurship offers a comprehensive, integrated, and proven step-by-step approach to creating innovative, highly succefful products